Simulation of Concrete Slab Behavior to Explosion - M. Shahib Al Bari; Januarti Jaya Ekaputri; F. Faimun; Julendra Bambang Ariatedja; Buntara S. Gan (Journal of Infrastructure & Facility Asset Management, 2019)
Special structure prone to explosion requires special material. Identification of special material is required to find the right concrete properties. Researching material behavior using explosion test is costly. Therefore, prediction using simulation is needed. In this study, we use ANSYS Workbench as a simulation program. The explosion test model comprised a non-reinforced slab 500×500×50 mm and TNT cube. It was found that the compressive strength minimum of the concrete slab that withstand the explosion of 30 grams TNT was 20 MPa. The Young modulus affects to the concrete behavior using default RHT Concrete properties. It had instability against modified concrete properties when performing numerical analysis.